ISOTOPIC PARTITIONING BETWEEN SCALLOP SHELL CALCITE AND SEAWATER: EFFECT OF SHELL GROWTH RATE - Owen R.; Kennedy H.; Richardson C. (My University, 2002)
The relationship between molluscan shell growth rate and skeletal δ18O and δ13C was investigated in a detailed field study for the scallop, Pecten maximus. Seasonal variation in shell growth rate was found to be a governing factor influencing shell δ18O and δ13C. At low shell growth rates, shell δ18O were more positive (of the order +0.4%%) and δ13C more negative (up to -2%%) as compared with predicted values for precipitation of inorganic calcite in isotopic equilibrium with seawater. The deviations in δ18O were hypothesized as reflecting possible differences in solution carbonate chemistry at the site of mineralization in the extrapallial fluid as compared with that of the external seawater medium. The deviations in shell δ13C were consistent with incorporation of isotopically depleted respiratory 13C (i.e., a metabolic effect). A trend toward more depleted shell δ18O and δ13C values occurred at higher shell growth rates, with negative δ18O values as compared with predicted equilibrium at shell growth rates above 0.13 mm per day. These simultaneous negative deviations in skeletal δ18O and δ13C were interpreted as resulting from a kinetic effect. The implications for environmental reconstruction from molluscan isotopic records are discussed in light of a model of isotopic behavior based on the findings of the study.